Current Status of the New Antiepileptic Drugs in Chronic Pain - Sidhu, Harpreet S.; Sadhotra, Akshay (Frontiers in Pharmacology, 2016)
Antiepileptic drugs (AEDs) are extensively used worldwide to treat a wide range of disorders other than epilepsy, such as neuropathic pain, migraine and bipolar disorder. Due to this situation more than 20 new third-generation AEDs have been introduced in the market recently. The future design of new AEDs must also have potential to help in the non-epileptic disorders. The wide acceptance of second generation AEDs for the management of various Non-epileptic disorders has caused the emergence of generics in the market. The wide use of approved AEDs outside epilepsy is based on both economic and scientific reasons. Bipolar disorders, migraine prophylaxis, fibromyalgia and neuropathic pain represent the most attractive indication expansion opportunities for anticonvulsant developers, providing blockbuster revenues. Strong growth in non-epilepsy conditions will see Pfizer’s Lyrica become the market leading brand by 2018. In this review we mainly focus on the current status of new AEDs in the treatment of chronic pain and migraine prophylaxis. AEDs have a strong analgesic potential and this is demonstrated by the wide use of carbamazepine in trigeminal neuralgia and sodium valproate in migraine prophylaxis. At present, data on the new AEDs for non-epileptic conditions are inconclusive. Not all AEDs are effective in the management of neuropathic pain and migraine. Only those AEDs whose mechanisms of action are match with pathophysiology of the disease, have potential to show efficacy in non-epileptic disorder. For this better understanding of the pathophysiology of the disease and mechanisms of action of new AEDs are essential requirement before initiating pre-clinical and clinical trials. Many new AEDs show good results in the animal model and open-label studies but fail to provide strong evidence at randomized, placebo-controlled trials. The final decision regarding the clinical efficacy of the particular AEDs in a specific non-epileptic disorder should be withdrawal from randomized placebo trials rather than open-label studies; otherwise this may lead to off-label uses of drug. The purpose of the present review is to relate the various mechanisms of action of new AEDs to pathophysiological mechanisms and clinical efficacy in neuropathic pain and migraine.